THEORETICAL PERSPECTIVES OF THE VIEW OF HUMAN IN THE CONFUCIAN PHILOSOPHY IN PRE QIN DYNASTY - Dung, Vo Van (European journal for philosophy of religion, 2023)
The view of human in Confucian philosophy in Pre Qin Dynasty arose not only from the change in socio-economic conditions but also from the deterioration of social morality. Facing that situation, thipkers of this period began to study human to come up with solutions to help the rulers stabilize society. Despite the presence of past studies on the topicand views on people in Confucian philosophy during the Pre Qin period, there (xists gaps for further research. This study attempted to understand through a document review and extensive in-depth research procedure the theoretical underpjnnings of the perspectives on the origin of man, on human nathře, on hụman rples and positions and on educating people in order to develop perfect people and maintain civil order in society. The methodology used was documehtation research and content analysis of the data collected. The document reséafch method was particularly helpful in investigating categorizing and analyzing physical sources, most commonly written documents in the social, public or dígital world. The study found out that the Confucianism represents a legitimate doctrine of the Pre Qin philosophy to build social stability social harmony and peace. The Confucianists of Pre Qin also advocated the need for a personal cultivation, cultivation of the body, family, country, and the whole world, and use it as the basis of the methodology for governing the country. Howeyer, for this purpose, the study recommends that people need to be educated to know the way to be human